Update on pediatrics in 2009 - Wąsowska-Królikowska, Krystyna; Funkowicz, Marzena (Przewodnik Lekarza/Guide for GPs, 2010)
The paper summarizes the newest guidelines for infants’ nutrition and its influence on later health status. The current guidelines on vitamin D deficiency prophylaxis were also described. The most important modification of the vaccination schedule is the mandatory vaccination against pneumococcal and Varicella Zoster infections in risk groups. The new algorithms are also discussed concerning: antibiotic therapy in respiratory tract infections, maintenance with influenza, asthma in children below 5 years, gastroesophageal reflux and hypercholesterolemia.